External factors and endogenous elements fostering critical thinking of tertiary EFL learners in China: a grounded theory study - Xinke, Song; Razali, Abu Bakar; Sulaiman, Tajularipin (Society for Research and Knowledge Management, 2024)
The cultivation of critical thinking (CT) skills is a fundamental aim within the realm of higher education. It assumes particular significance within the domain of Teaching English as a Foreign Language (TEFL). This study directs its focus on the Chinese tertiary TEFL context and endeavours to explicate what the external factors are, as well as endogenous elements and ways to foster students’ critical thinking. Methodologically, the study adopted grounded theory (GT) and drew upon qualitative data gathered through interviews with 36 participants, including both students and instructors recruited from prestigious universities, mid-tier colleges, and less developed college across China. The data analysis, utilizing NVivo12 software, encompasses a multilevel coding process, including open, axial, and selective coding, in accordance with the principles of GT. The outcome of this meticulous analysis results in the formulation of a comprehensive model revealing the interplay among external influences, endogenous elements, and ways to foster the development of CT skills among tertiary English as a Foreign Language (EFL) students. The implications of these findings extend pedagogically to multiple stakeholders within the tertiary TEFL context.